Aplikasi E-Customer Relationship Management berbasis Web sebagai Sarana dalam Penjualan Produk - Anggraeni, Nawang; Handayani, Masitah; Latiffani, Chitra (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The implementation of Electronic-Customer Relationship Management (E-CRM) requires synergy between information technology and the company's human resources. E-CRM serves to facilitate customers in obtaining relevant information from the company. This study aims to design and develop an E-CRM system to support online sales at Andari Kosmetik Store. This research employs a system development method using the waterfall model, which includes the stages of analysis, design, implementation, and testing. During the analysis stage, system requirements were identified to support the implementation of the E-CRM system. The design stage involved creating a use case diagram to visualize the interaction flow within the system. Implementation and testing were conducted directly using the black box testing method to evaluate the functionality of the developed system. The findings of this study reveal that the developed web-based E-CRM application is equipped with features such as chat, member management, and a voucher system, which simplify the purchasing process and support integrated transaction handling within the E-CRM system. This application is expected to enhance efficiency and customer satisfaction in their interactions with the company.